Genetic studies on collagenolytic achromobacter strains and their bacteriophages - Thomson, Jennifer Ann (Rhodes University, Faculty of Science, Botany Department, 1974)
From Summary: A survey of collagenolytic aerobic bacteria from cured hides yielded three strains of Bacillus and eight of Achromobacter which degraded collagen at 0.4 M NaCl. Achromobacter sp. 2 was chosen for genetic studies due to its high collagenolytic activity and the lack of genetic information on Achromobacter. Four temperate bacteriophages specific for Achromobacter sp. 2 were isolated and their relationships studied. The phages caused lysogenic conversion resulting in the inability of lysogens to adsorb phage. Achromobacter sp. 2 was shown to be a cryptic lysogen as it was not immune to superinfection but had a very low rate of spontaneous induction which could be increased with mutagens. It is proposed that the cryptic lysogeny of this strain is maintained by a defective excision mechanism and the mode of prophage integration in the host chromosome. DNA extracted from phage Î±3a was used to transfect spheroplasts. The optimal conditions for the development of competence for transfection were determined. The presence of nuclease-attack on phage DNA under conditions of prolonged incubation of DNA and spheroplasts was proposed. A method for extracting Achromobacter DNA was devised which yielded purified, undegraded DNA, but it was not possible to transform Achromobacter sp. 2 with this DNA. The a phages were used to transduce a number of genetic markers into Achromobacter auxotrophs. The transduct ants had the ability to release the cryptic Î±3 prophage at a high rate while maintaining their sensitivity to homologous phage infection. It is proposed that this is due to complementation between the cryptic prophage and the residual phage functions in the transducing particles. The transductants segregated auxotrophs with a probability of 10â »Â³ per cell per generation. It appears that an unusual system of generalised transduction is operating whereby the transducing particles contain both phage and bacterial DNA which is incorporated into the recipient genome by a single recombination event yielding unstable transductants. In a study on induction of Escherichia coli (Î»), carcinogenic nitrosamines were shown to be inducers of phage development. This provides a screening system for potentially harmful nitrosamines.
Keywords: Bacteriophages -- Genetics; Bacterial genetics